Spectroscopic Kernel Quality from a Symbiotic Corn Production - Masoero, Giorgio; Mazzinelli, Gianfranco; Balconi, Carlotta; Locatelli, Sabrina; Lanzanova, Chiara; Ardigò, Annamaria; Giovannetti, Giusto; Volpato, Silvia; Nuti, Marco (Journal of Agronomy Research, 2020)
The management of the inoculation of a plant’s roots, by means of biofertilizers (BF) containing arbuscular mycorrhizal (AM) fungi, is aimed at inducing modifications of the quality of the seeds. It is here shown that a seed-soil treatment can be elicited in the fingerprints of a symbiotic treatment using Near Infra Red (NIR)-SCiO  NIR-SCiO spectra collections of single kernels: overall, a sensitivity of 73% and a specificity of 73% have been achieved, thus suggesting that it may be possible to assign the symbiotic origin of corn from just twenty kernels, provided that the dataset is adequately representative of the cultivar and AM. A global correlation study has shown a positive general trend (R2 0.45) of quality vs. quantity, in the sense that an increase in yield corresponded to an increase in the spectral differences between the symbiotic spectra and the control ones, but the inverse was also true, as a result of the parasitic behaviour of the BF treatments. The efficacy of the symbiosis can be back predicted from the NIR spectra; in fact, around 90% of the positive yield outcome results were discriminated from the negative ones. A reduction in the foliar pH (R2 0.37) and an increase in the foliar protein (R2 0.43) were observed as immediate phenotypic signs of a productive symbiosis. The commercial raw composition of the kernels appeared to only be affected slightly by the BF treatments; thus, till now uncharted secondary compounds of the maize kernels are involved, as supported by animal performances.
Keywords: Biofertilizers; Fingerprinting; NIRS; SCiO; Maize; Kernel; Quality; Symbiotic response.